2013
DOI: 10.1530/eje-12-0631
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of eplerenone or spironolactone treatment in preserving renal function in primary aldosteronism

Abstract: Objective: Primary aldosteronism (PA) has deleterious effects on kidney function independent of blood pressure levels. Up to now, data on effectiveness of different PA therapies regarding renal function are scarce. Design and methods: This prospective multi-center study included 29 patients with newly diagnosed PA evaluated before and 1 year after treatment initiation, and a second cohort including 119 patients who were evaluated 5.3 and 6.8 years after treatment initiation. Glomerular filtration rate (GFR), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 44 publications
1
43
1
Order By: Relevance
“…The German Conn's Registry (www.conn-register.de) is a multi-center database analyzing comorbidities and longterm outcome of patients with PA (4,13,14). Since the initiation of the prospective phase in October 2008, all patients actively treated within the centers were entered in a common database after pseudonymization (15).…”
Section: Design and Patientsmentioning
confidence: 99%
“…The German Conn's Registry (www.conn-register.de) is a multi-center database analyzing comorbidities and longterm outcome of patients with PA (4,13,14). Since the initiation of the prospective phase in October 2008, all patients actively treated within the centers were entered in a common database after pseudonymization (15).…”
Section: Design and Patientsmentioning
confidence: 99%
“…50 Five other studies, with spironolactone uptitrated as needed and tolerated, revealed effects no different from those of surgery. [44][45][46]48,53,55 PA patients treated with spironolactone or amiloride experience an improvement in wellbeing similar to that observed after adrenalectomy, although these effects appear to be established more slowly. 86 …”
Section: Outcomes Of Drug-based Treatmentmentioning
confidence: 81%
“…40 They are most marked in patients with unilateral PA 41,42 and are reversed within one month of adrenalectomy (Figure 1). 40,[43][44][45][46][47][48][49][50][51][52][53][54][55] Hemodynamic stress and hyperaldosteronism per se lead to chronic structural damage in the long run. 45,56 PA patients have been reported to display a certain level of insulin resistance, which may improve after adrenalectomy.…”
Section: Outcomes Of Adrenalectomy In Unilateral Pamentioning
confidence: 99%
See 1 more Smart Citation
“…A short-term (1 year) study suggested superiority of surgery over medical treatment with regard to glomerular filtration rate and proteinuria [32]. However, long-term (> 5 years) renal benefit of medical treatment seems not inferior to surgery [33][34][35].…”
Section: Infraclinical Renal Damagementioning
confidence: 99%